BPD Following Preterm Birth: A Model for Chronic Lung Disease and a Substrate for ARDS in Childhood - Bhandari, Anita; Carroll, Christopher; Bhandari, Vineet (Frontiers in Pediatrics, 2016)
It has been suggested that pediatric acute respiratory distress syndrome (PARDS) may be a different entity, vis-à-vis adult ARDS, based on its epidemiology and outcomes. A more pediatric-specific definition of PARDS to include the subgroup of patients with underlying lung (and heart) disease has been proposed. Epidemiologic data suggests that up to 13% of the children with ARDS have a history of prematurity and/or underlying chronic lung disease. However, the specific contribution of bronchopulmonary dysplasia (BPD), the most common chronic lung disease in infants, to the development of PARDS is not known. BPD leads to damaged lungs with long-term consequences secondary to disordered growth and immune function. These damaged lungs could potentially act as a substrate, which given the appropriate noxious stimuli, can predispose a child to PARDS. Interestingly, similar biomarkers (KL-6, IL-6, IL-8, sICAM-1, Angiopoietin-2, MMP-8 and -9) of pulmonary injury have been associated both with BPD and ARDS. Recognition of a unique pattern of clinical symptomatology and/or outcomes of PARDS, if present, could potentially be useful for investigating targeted therapeutic interventions.